2010
DOI: 10.1016/s0929-6646(10)60076-9
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Readmission Among Ventilator-dependent Patients After Successful Weaned Discharge From a Respiratory Care Ward

Abstract: Underlying comorbidities and causes of ventilator dependency are important predictors of mortality and readmission among patients after weaned discharge from a RCW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 30 publications
0
18
0
3
Order By: Relevance
“…Younger age is significantly associated with greater long-term survival, and the risk of mortality increases 1.3-fold with every 10-year increase in age 23 . Hui et al reported that 67.1% of weaned patients were readmitted within 3 months of discharge and that the most common cause of readmission was airway infection (80.5%) 24 . Patients with cardiac and pulmonary disease as causes of respiratory failure had higher readmission probability.…”
Section: Discussionmentioning
confidence: 99%
“…Younger age is significantly associated with greater long-term survival, and the risk of mortality increases 1.3-fold with every 10-year increase in age 23 . Hui et al reported that 67.1% of weaned patients were readmitted within 3 months of discharge and that the most common cause of readmission was airway infection (80.5%) 24 . Patients with cardiac and pulmonary disease as causes of respiratory failure had higher readmission probability.…”
Section: Discussionmentioning
confidence: 99%
“…[5,811] Home and RCW caregivers of PMV patients have different concerns. Previous studies have revealed that caregivers of patients receiving institutional care are concerned about patients’ health status and future medical care requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Dentre os estudos desta revisão, destacou--se a VMP e o desmame prolongado como prin-cipais preditores de mortalidade (13,17,18,(20)(21)(22)29,32) . A ocorrência de VMP pode ser influenciada por comorbidades crônicas pré-existentes na admissão, dentre as quais destacam-se doença renal crônica, diabetes mellitus, doença cerebrovascular e doença pulmonar (13,17,18) . Um estudo observacional (19) , com 7848 pacientes em uso de VMI, identificou que as causas infecciosas, como pneumonia e choque séptico, também determinam a dependência do ventilador.…”
Section: Discussionunclassified
“…Um estudo observacional (19) , com 7848 pacientes em uso de VMI, identificou que as causas infecciosas, como pneumonia e choque séptico, também determinam a dependência do ventilador. Estes fatores repercutem em maiores taxas de readmissões, maior tempo de internação hospitalar (17,19) , prolongamento do desmame e extubação (20)(21)(22) , visto que a recuperação é mais lenta em pacientes com doenças crônicas complexas e/ou infecciosas (13) . Fonte: dados referentes à complicação da busca nas bases de dados…”
Section: Discussionunclassified